Transformative Islamic Education in the Perspective of Kuntowijoyo’s Prophetic Social Sciences in the Society 5.0 Era - Sandi Ferdy Yulianto; Ninik Zuroidah; Najihatul Fadhliyah (Edudeena : Journal of Islamic Religious Education, 2025)
This study aims to analyze the implementation of Kuntowijoyo’s three pillars of Prophetic Social Sciences, namely humanization, liberation, and transcendence, in realizing transformative Islamic education at MAN 4 Kediri within the context of the Society 5.0 era. The research is grounded in the need for Islamic educational institutions to balance rapid digital development with the cultivation of character, spirituality, and social awareness so that students are able to respond comprehensively to contemporary global challenges. Using a qualitative approach with a field-based case study design, data were collected through non-participatory observations, in-depth interviews, and documentation involving the principal, teachers, education staff, and students. The findings reveal that humanization is manifested through the 5S culture, dialogical learning, student empowerment, and supportive social relations. Liberation appears through pedagogical autonomy, student participation in decision making, the integration of digital learning technologies, and egalitarian policies for education staff. Meanwhile, transcendence is expressed through structured worship routines, weekly religious activities, and the strengthening of a spiritually oriented school climate. These findings confirm that MAN 4 Kediri has successfully integrated prophetic values as the foundation of a transformative, relevant, and adaptive Islamic education model. The study’s limitation lies in its single case scope, indicating the need for comparative and longitudinal research. This research contributes originality by providing an empirical mapping of how the prophetic paradigm is applied in contemporary Islamic education practice.